Infectious lesions of placenta as cause of miscarriage - A. V. Kolobov; A. I. Merkulova; V. A. Tsinzerling (Журнал инфектологии)
Analysis of the literature demonstratesimportant role played of infections in causes of miscarriage. The paper is based upon retrospective analysis of 12371 screening results of histological and selective immunohistochemical studies of placentas in 2009-12. Preterm births were in 706 cases (5.71%). Infection of the placenta was noted in early preterm labor in all cases (100%), and in premature labor at 28-36 weeks of gestation – in 97.35% of natural delivery cases and in 92.09% when cesarean delivery. Are described the typical structural changes that allow to suspect infections caused by Treponema pallidum, herpes viruses, human immunodeficiency virus, parvovirus with following verification by immunohistochemical study.